If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -5y) + -1(2x + 5y) = 0 Remove parenthesis around (2x + -5y) 2x + -5y + -1(2x + 5y) = 0 2x + -5y + (2x * -1 + 5y * -1) = 0 2x + -5y + (-2x + -5y) = 0 Reorder the terms: 2x + -2x + -5y + -5y = 0 Combine like terms: 2x + -2x = 0 0 + -5y + -5y = 0 -5y + -5y = 0 Combine like terms: -5y + -5y = -10y -10y = 0 Solving -10y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-10'. y = 0.0 Simplifying y = 0.0
| X^3-21x+10=0 | | x^2+20x+90=0 | | 10+x-1/3=0 | | -64x^2+176x-121=0 | | (w^2)-w=36+4w | | (c^2)=16 | | 39.6=5.5l | | x/3-1.2=-1.566 | | -11=4-4x | | 3(7x-21)=-14 | | 9x+7=2(3x+8) | | -9y=-117 | | 24x-7=4x+3 | | n/28=3/7 | | 2=4x-ygraph | | -33.84=7.2n | | 3t+s=58 | | 570x=9000+9x^2 | | 15-8x=11-7x | | 2x+84=14x | | 4x+12=5x+1 | | 580x=12000+7x^2 | | 8(-x+10)=100 | | 4x+3=-3x+29 | | 3x+15=18x | | 3x=99-8x | | -13=-4(x-4)+9(x-6) | | x(x+1)(5x+4)=0 | | 3x-3=-4x+25 | | 6h(7h+19)=0 | | 2(2x+8)-11=7 | | 5x^4-180x^2=0 |